Sustainability education in indian business schools: a status review (2016)
Sustainability issues, given their potential scale of impact and urgency, have captured the imagination of both corporations and academic institutions everywhere. This paper examines how such problems and their potential solutions have been incorporated into higher education, particularly business school education in India. With over 3,600 business schools in the public and private sector, business education in India has proliferated. However, students by and large still remain unexposed to sustainability and disaster management concepts in their curriculum.  The underlying factors for this include, lack of institutional capacity, issues related to faculty motivation and incentives, lack of recruiter interest and limited availability to high quality resource material.  Further, while several schools in India focus on sectors relevant to sustainability, inter-organizational linkages have not developed and business school generally operate independently.  This paper examines the way forward to deeply integrate sustainability principles into the core curriculum of business schools. Measures suggested include creating communities of practice among academia and industry, building a resource base of teaching materials for easy access by faculty, and several measures to strengthen institutional capacity.